Reduced frontal gamma power at 24 months is associated with better expressive language in toddlers at risk for autism. Issue 8 (22nd May 2019) - Wilkinson, Carol L.; Levin, April R.; Gabard‐Durnam, Laurel J.; Tager‐Flusberg, Helen; Nelson, Charles A.
Abstract : Frontal gamma power has been associated with early language development in typically developing toddlers, and gamma band abnormalities have been observed in individuals with autism spectrum disorder (ASD), as well as high‐risk infant siblings (those having an older sibling with ASD), as early as 6 months of age. The current study investigated differences in baseline frontal gamma power and its association with language development in toddlers at high versus low familial risk for autism. Electroencephalography recordings as well as cognitive and behavioral assessments were acquired at 24 months as part of prospective, longitudinal study of infant siblings of children with and without autism. Diagnosis of autism was determined at 24–36 months, and data were analyzed across three outcome groups—low‐risk without ASD ( n = 43), high‐risk without ASD ( n = 42), and high‐risk with ASD ( n = 16). High‐risk toddlers without ASD had reduced baseline frontal gamma power (30–50 Hz) compared to low‐risk toddlers. Among high‐risk toddlers increased frontal gamma was only marginally associated with ASD diagnosis ( P = 0.06), but significantly associated with reduced expressive language ability ( P = 0.007). No association between gamma power and language was present in the low‐risk group. These findings suggest that differences in gamma oscillations in high‐risk toddlers may represent compensatory mechanisms associated with improved developmental outcomes. Autism Res 2019, 12: 1211–1224 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study looked at differences in neural activity in the gamma range and its association with language in toddlers with and without increased risk for ASD. At 2 years of age, gamma power was lower in high‐risk toddlers without ASD compared to a low‐risk comparison group. Among high‐risk toddlers both with and without later ASD, reduced gamma power was also associated with better language outcomes, suggesting that gamma power may be a marker of language development in high‐risk children.